2006
DOI: 10.1111/j.1556-4029.2006.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and High‐Throughput Forensic Short Tandem Repeat Typing Using a 96‐Lane Microfabricated Capillary Array Electrophoresis Microdevice*

Abstract: A 96-channel microfabricated capillary array electrophoresis (muCAE) device was evaluated for forensic short tandem repeat (STR) typing using PowerPlex 16 and AmpFlSTR Profiler Plus multiplex PCR systems. The high-throughput muCAE system produced high-speed <30-min parallel sample separations with single-base resolution. Forty-eight previously analyzed single-source samples were accurately typed, as confirmed on an ABI Prism 310 and/or the Hitachi FMBIO II. Minor alleles in 3:1 mixture samples containing femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 26 publications
(28 reference statements)
5
50
0
Order By: Relevance
“…In addition, Yeung et al [56] reported on high-throughput DNA analysis presenting a 96-channel microfabricated capillary array system, which was evaluated for STR analysis. The system produced ,30 min parallel separations with single-base resolution and high accuracy, as proved by parallel analysis with validated systems.…”
Section: Forensic Dna Analysismentioning
confidence: 99%
“…In addition, Yeung et al [56] reported on high-throughput DNA analysis presenting a 96-channel microfabricated capillary array system, which was evaluated for STR analysis. The system produced ,30 min parallel separations with single-base resolution and high accuracy, as proved by parallel analysis with validated systems.…”
Section: Forensic Dna Analysismentioning
confidence: 99%
“…Thus, these issues with short separation channels could be alleviated through the use of a smaller set of short amplicons that do not require such long separation channels. Such a sample set would be ideal for application with microfluidic devices and would fit the need for a rapid onsite screening tool [25].…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput microfabricated capillary array electrophoresis (mCAE) STR analysis system [9] is used for evaluating these reagents. The spectroscopic properties and performance of each ET-labeled primer and ETlabeled single-locus PCR product(s) were compared to those labeled with their corresponding single fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%